2008
DOI: 10.1172/jci32865
|View full text |Cite|
|
Sign up to set email alerts
|

Curcumin prevents and reverses murine cardiac hypertrophy

Abstract: Chromatin remodeling, particularly histone acetylation, plays a critical role in the progression of pathological cardiac hypertrophy and heart failure. We hypothesized that curcumin, a natural polyphenolic compound abundant in the spice turmeric and a known suppressor of histone acetylation, would suppress cardiac hypertrophy through the disruption of p300 histone acetyltransferase-dependent (p300-HAT-dependent) transcriptional activation. We tested this hypothesis using primary cultured rat cardiac myocytes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
91
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(92 citation statements)
references
References 44 publications
(31 reference statements)
1
91
0
Order By: Relevance
“…We and others (14,15) have recently reported that a p300-specific HAT inhibitor, curcumin, can prevent the development of cardiomyocyte hypertrophy and heart failure in vivo. The present study provides evidence that Cdk9 kinase activity is required for p300 HAT activity and for the p300/GATA4 transcriptional pathway during hypertrophic responses in cardiomyocytes.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…We and others (14,15) have recently reported that a p300-specific HAT inhibitor, curcumin, can prevent the development of cardiomyocyte hypertrophy and heart failure in vivo. The present study provides evidence that Cdk9 kinase activity is required for p300 HAT activity and for the p300/GATA4 transcriptional pathway during hypertrophic responses in cardiomyocytes.…”
Section: Discussionmentioning
confidence: 83%
“…HAT activity of p300 is required for myocardial hypertrophy in vitro and for the promotion of left ventricular remodeling in vivo (13). Recently, we and others have reported that a natural p300-specific HAT inhibitor, curcumin, prevents the development of cardiomyocyte hypertrophy and heart failure in vivo, further emphasizing the importance of p300 in these processes (14,15). In addition, p300 acts as a scaffold protein in the assembly of multisubunit transcription factor complexes for specific cardiac promoters, thereby conferring further specificity.…”
mentioning
confidence: 99%
“…The difference observed can account for genetic diversity of Lippia multiflora (Adou et al, 2011) at certain level in addition to the effect of the latitude variation (Purseglove, Brown, Green, & Robbins, 1981). However, environment effect as described by Besombes (2008) can stand out among variability factors of essential oil quality in a restricted area as much as our studied region. Soil contents of P as total and available P has shown significant influences on the concentrations of major volatile substances determined in extractable essential oils across the studied sites.…”
Section: Essential Oil and Soil Relationshipmentioning
confidence: 82%
“…Previous studies have shown that curcumin selectively inhibits ectopic fVII synthesis by removing p300/CBP from the FVII promoter region. Furthermore, animal studies have shown that curcumin can cure cardiovascular diseases [114,115] and cancer [116] by targeting p300 activity. Therefore, anti-p300 strategies using curcumin may be clinically applicable, without posing significant toxicity.…”
Section: Summary and Perspectivesmentioning
confidence: 99%